A Study on Tourism Industries and Customer Relationship Marketing: An Overview of the Growth and Impact of Tourism Industries in India (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Tourism in India has registered significantgrowth in the recent years. In 1951, international tourist arrival stood ataround 17 thousand only while the same has now gone up to 3.91 million in 2005.The upward trend is expected to remain firm in the coming years. Tourism is thethird largest net earner of foreign exchange for the country recording earningsof US$ 5731 million in 2005, a growth of 20.2 percent over 2004. Tourism is also one of the sectors, whichemploys the largest number of manpower. According to the Ministry of Tourism,during January - December of the calendar year 2006 total tourist inflow stoodat 44,299,15 as against 39,186,10 in the same period of the last year.